1997
DOI: 10.1111/j.1460-2695.1997.tb00291.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐temperature Autofrettage: An Improved Technique to Enhance the Fatigue Resistance of Thick‐walled Tubes Against Pulsating Internal Pressure

Abstract: It is shown that autofrettage at low temperatures is superior to autofrettage at room temperature in enhancing the fatigue resistance of thick-walled tubes against pulsating internal pressure. The physical reason is based on the well-known temperature dependence of the mechanical behaviour of metals and alloys which generally exhibit an enhancement of both the yield stress and strain hardening behaviour at lower temperatures. As a consequence, significantly larger compressive residual hoop stresses can be intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…The latter is essentially based on the (repeated) application of a high internal pressure in a thick-walled tube, causing partial yielding of the tube from the inner bore into the cross section. After autofrettage, a beneficial residual triaxial stress state whose most important component is a tangential (hoop) compressive stress is retained in the inner part of the tube (see, e.g., [1][2][3][4][5][6][7][8][9][10][11][12][13][14]).…”
Section: Introductionmentioning
confidence: 99%
“…The latter is essentially based on the (repeated) application of a high internal pressure in a thick-walled tube, causing partial yielding of the tube from the inner bore into the cross section. After autofrettage, a beneficial residual triaxial stress state whose most important component is a tangential (hoop) compressive stress is retained in the inner part of the tube (see, e.g., [1][2][3][4][5][6][7][8][9][10][11][12][13][14]).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies have shown that fatigue strength can be greatly increased through application of autofrettage processes. Application of a low temperature autofrettage process was found to result in a greater than 40% increase in fatigue limit . Other autofrettage studies have reported fatigue strength increase in excess of 60% .…”
Section: Introductionmentioning
confidence: 90%
“…Component surfaces that are exposed to high tribological loads, such as shaft counter surfaces for radial shaft seals, must have high hardness in the surface layer and at the same time a sufficient bulk toughness to guarantee their functionality [2]. For non-brittle materials like stainless austenitic steel, a high hardness in the workpiece surface layer also results in a longer service life of cyclically stressed components, because the crack initiation is hampered and the crack propagation rate is reduced [3][4][5]. Usually, workpieces are post-processed after machining by a subsequent heat treatment or a mechanical hardening process in order to increase the hardness of the workpiece surface layer.…”
Section: Introductionmentioning
confidence: 99%